2015
DOI: 10.1016/j.otsr.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Complex regional pain syndrome type I in children. Clinical description and quality of life

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 20 publications
0
21
0
2
Order By: Relevance
“…The precise cellular mechanisms underlying CRPS remain elusive; however, we know it to be a highly incapacitating chronic pain syndrome. A history of physical trauma and psychosocial stressors has been identified as a risk factor for CRPS in pediatric patients 5 . Iniguez et al found that 49% of pediatric patients with CRPS had experienced physical trauma, and 51% reported at least 1 psychosocial stressor 5 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The precise cellular mechanisms underlying CRPS remain elusive; however, we know it to be a highly incapacitating chronic pain syndrome. A history of physical trauma and psychosocial stressors has been identified as a risk factor for CRPS in pediatric patients 5 . Iniguez et al found that 49% of pediatric patients with CRPS had experienced physical trauma, and 51% reported at least 1 psychosocial stressor 5 .…”
Section: Discussionmentioning
confidence: 99%
“…A history of physical trauma and psychosocial stressors has been identified as a risk factor for CRPS in pediatric patients 5 . Iniguez et al found that 49% of pediatric patients with CRPS had experienced physical trauma, and 51% reported at least 1 psychosocial stressor 5 . Furthermore, quality of life in pediatric patients with CRPS type I has been assessed using the Pediatric Quality of Life (PEDS QL) 4‐0 score, revealing significantly lower scores than the control group regarding physical, psychosocial, social, and emotional aspects, sparing the school performance, which was found to be unaffected 5 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Physical functioning was not assessed by medical provider evaluation, but by parental survey. The PedsQL™ is an inventory not approved specifically for OI, but has been used in other chronic pediatric disease-specific populations [ 28 , 29 ]. The FACES® scale used to evaluate pain is not specific for a population with OI; unfortunately, there is no pain assessment available specifically for children and adolescents with OI [ 30 ].…”
Section: Discussionmentioning
confidence: 99%